P466 Is it possible avoid colectomy with rescue dual therapy with vedolizumab plus tacrolimus in ulcerative colitis that losing response to anti-tumour necrosis factor?. (15th January 2020) - Sanchis, L; Molés, J R; Borrás, J; Rodriguez, J; Cortés, X
Abstract: Background: There is an increasing number of ulcerative colitis (UC) patients that losing response to anti-tumour necrosis factor (TNF) drugs. There is low evidence about combining Tacrolimus (TAC) with vedolizumab (VED) for UC patients, who have failed treatment with anti-TNF therapy. The aim of the present study was to assess the efficacy and safety of TAC with VED in UC patient refractory to anti-TNF therapies. Methods: Inclusion criteria: patients with moderately to severely active UC and who failed or showed intolerance to at least one TNF antagonists that received dual therapy with VED and oral TAC (Envarsus ® ). TAC blood levels were monitored at weeks 2, 4, 8 and then every 2 months. Rates of clinical response and remission were evaluated in November 2019 using the Mayo score. Clinical response was considered when PCR and calprotectin were decreased ³50% and biological remission was considered when PCR and calprotectin achieved normal values. Results: Seven UC patients (1 proctitis, 3 left colon disease, 2 Pancolitis and 1 pouchitis) had sufficient dTNF for analysis. Demographic dTNF: age 51 ± years and 10.4 ± years since UC was diagnosed. All patients received thiopurine therapy and 86% received corticosteroids. 43% of patients were corticodependent and 43% were corticosteroid-refractory. 29% of patients failed to one TNF antagonists and 71% of patients failed to two TNF antagonists. Previous to started dual therapy; 29% of patients with moderate endoscopic activity and 71% of patients with severe endoscopic activity. Thiopurine treatment was suspended and 3 corticosteroid-refractory patients received IV cyclosporine therapy. The median dual therapy follow-up was 12.8 months (range 6–30 months). At the end of the study period; all patients presented clinical response, 86% of patients were corticosteroids free and biological remission was achieved in 71% of patients and any patient required colectomy. Fifty-seven per cent of patients needed VED dose intensification. Side effects were mild; abdominal pain (1), tremor (4), hypertension (1), moderate decrease creatinine clearance (1), insomnia (1) and arthralgías (1). Any patient discontinued dual therapy by adverse drug effect. At the end of the study, 4 patients continued with the dual therapy and 3 patients TAC was discontinued due to maintained clinical remission Conclusion: In UC patients that losing response to anti-tumour necrosis factor (TNF) drugs and corticosteroid-refractory, the dual therapy with VED plus TAC could be an alternative, effective and safe therapy.